Hubungan Asupan Karbohidrat Dan Lemak Dengan Tebal Lemak Bawah Kulit Pada Siswi SMA N 6 Yogyakarta - SARI, Anita Wulan; , Toto Suharto, SKM., M.Kes; , Elida Soviana, S.Gz., M.Gizi (2015)
Background: Teens are more nutritional status will cause malfunctioning of the body and is a risk factor for disease in adulthood.Carbohydrate and fat intake contributed the largest energy for the body that will be stored as fat tissue. The fat tissue can be measured with a skinfold caliper. Objective: Analyzing thecorrelation of carbohydrate and fat intake with subcutaneous fat thickness on female students of SMA N 6 Yogyakarta. Research methods: This type of research is observational research with cross sectional study design. The study was conducted in SMAN 6 Yogyakarta in November 2014. The number of samples is 44 female students were taken by systematic random sampling. Carbohydrate and fat intake measured with 3x24hour of form record. Subcutaneous fat thickness measured with a skinfold caliper. Data analysis with Pearson Product Moment correlation test. Result: Female student's carbohydrate intake per day on average 219 grams and the majority are included in the category of severe deficiency (38.6%). Female student's fat intake per day on average 68.03 grams and a majority is included in the normal category (38.6%). subcutaneous fat thicknessof female student average on 62.48 mm and the majority of moderate categorized are 56.8%. Conclusion: There is correlation between carbohydrate intake and thick subcutaneous fat with p = 0.018. There is correlationbetween the intake of fat and subcutaneous fat thickness with a value of p = 0.034.